Improving The Competence Of North Sumatra French Teachers Through Assistance In Preparing Merdeka Curriculum Learning Tools - Tengku Ratna Soraya; Junita Friska; Rahmad Husein; Rizki Fadila Nasution (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to provide solutions to the problems faced by partners, namely the lack of understanding of the implementation of the Merdeka curriculum, especially in designing and compiling Merdeka Curriculum teaching tools in high schools and vocational schools that implement French as an optional language taught.  Therefore, the community service team provided assistance in understanding the Merdeka curriculum. The activity was carried out in three stages, namely first 'training / exposure to the concept of Merdeka curriculum for French-speaking high schools and vocational schools which includes exposure to the design of play activities with reference to learning outcomes; Exposure to the development of learning pathways and objectives in French-speaking high school and vocational units based on unit characteristics, children's needs and interests, environmental conditions, and their relationship with learning outcomes, so that the learning pathways and objectives between each unit can be different; Exposure to developing student worksheets according to the learning needs of students.  Second, assistance in making learning concept maps for French-speaking high schools and vocational schools, and third, practice in implementing teaching tools in front of peers. The output of this activity is an increased understanding of the concepts and ways of implementing the Merdeka Curriculum for French-speaking high schools and vocational schools. The teachers were very enthusiastic in participating in the training, they responded that with this training they could implement the Merdeka curriculum in their respective schools.